Assessing ecosystem services for informing land-use decisions: a problem-oriented approach - Förster, Johannes; Barkmann, Jan; Fricke, Roman; Hotes, Stefan; Kleyer, Michael; Kobbe, Susanne; Kübler, Daniel; Rumbaur, Christian; Siegmund-Schultze, Marianna; Seppelt, Ralf; Settele, Josef; Spangenberg, Joachim H.; et al. (Ecology and society, 2015)
Assessments of ecosystem services (ES), that aim at informing decisions on land management, are increasing in number around the globe. Despite selected success stories, evidence for ES information being used in decision making is weak, partly because ES assessments are found to fall short in targeting information needs by decision makers. To improve their applicability in practice, we compared existing concepts of ES assessments with focus on informing land use decisions and identified opportunities for enhancing the relevance of ES assessments for decision making. In a process of codesign, building on experience of four projects in Brazil, China, Madagascar, and Vietnam, we developed a step-wise approach for better targeting ES assessments toward information needs in land use decisions. Our problem-oriented approach aims at (1) structuring ES information according to land use problems identified by stakeholders, (2) targeting context-specific ES information needs by decision makers, and (3) assessing relevant management options. We demonstrate how our approach contributes to making ES assessments more policy relevant and enhances the application of ES assessments as a tool for decision support.